Causal Model of Problematic Internet Use Based on Basic Psychological Needs by Mediating Emotion Regulation and Avoidance Coping Strategies - Mehrnoosh Mottahedin; Fariborz Dortaj; Fatemeh Ghaemi; Reza Ghorban Jahromi (مطالعات رسانه‌های نوین, 2023)
IntroductionThe use of the internet has impacted various facets of human life, and its uncontrolled use is linked to multiple risks such as personal and social harms. With increased needs for internet use, alongside its benefits, the likelihood of problems, particularly Problematic Internet Use (PIU) among youth and students, rises. PIU can be caused by engaging in uncontrolled use, such as gaming, consuming adult content, or using social networking platforms. Internet addiction is characterized by obsessive and uncontrolled use of virtual programs that can lead to significant disruption and dysfunction in users' psychological, social, academic, and occupational functioning. Consequently, this study seeks to understand the impact of various variables, such as cognitive emotion regulation strategies, avoidance coping, and basic psychological needs, on PIU. The study aims to investigate whether emotion regulation and avoidance coping strategies play a mediating role in the association between basic psychological needs and PIU.2. Literature ReviewA review of the literature indicates that addictive behaviors are commonly associated with inadequate positive emotion regulation strategies and ineffective coping with emotions, particularly in the initial stages of addiction (Clarke et al., 2020, pp.21-22). Additionally, studies have suggested that when individuals experience distress, avoidance coping strategies may lead to adverse circumstances that provoke negative emotions, causing people to spend more time on the internet to evade them (Piri et al., 2019, p.44). Furthermore, research findings demonstrate a negative correlation between internet addiction and problem-focused coping strategies, and a positive correlation between emotion-focused and avoidance coping strategies (Bahadori et al., 2011, p.183).3. MethodologyThe research method used in this study is a descriptive, correlational approach that aimed to investigate the relationship between internet addiction, cognitive and emotional regulation strategies, basic psychological needs, and coping mechanisms. The study population was all students from the Islamic Azad University, Central and Karaj Branches, with an estimated total of 25,000 individuals. The sampling method used was a multi-stage cluster sampling approach, where three clusters were randomly selected from the Islamic Azad University, including the Central and Karaj Branches. In the next stage, three classes were randomly selected from each of the faculties of Humanities, Engineering, and Basic Sciences. The sample size was determined using the Cochran formula and calculated to be 380, but it was increased to 400 to ensure sample size suitability. Ultimately, 397 questionnaires were analyzed. The data collection tools used included the Internet Addiction Test (Kaplan, 2010), the Cognitive Emotion Regulation Questionnaire (Garnefski et al., 2001), the Basic Psychological Needs Scale (Gagne, 2003), and the Coping Inventory for Stressful Situations (Endler & Parker, 1990). The background and theoretical foundations section of the study was based on library research, while the numerical data collection section was based on field research using questionnaires. To ensure confidentiality, privacy, and integrity, ethical research principles were followed throughout the study, including confidentiality, privacy, and integrity. The data were analyzed using path analysis, and the SPSS and AMOS software were utilized.4. ResultsIn this study, a total of 397 participants were included, with 34% being male and 66% being female. The majority of participants (49%) reported being single, while 41% were married, and 10% were divorced. In terms of educational level, 44% were undergraduate students, and 56% were graduate students. The mean age of participants was 28.75, with a standard deviation of 3.12. The inferential findings revealed that avoidance coping had the highest correlation coefficient (0.42) with pathological internet use, followed by relatedness (0.26), adaptive coping strategies (0.23), competence (-0.14), maladaptive coping strategies (-0.14), and autonomy (0.12). Furthermore, the direct effect of autonomy on adaptive coping strategies was significant (0.30, p < 0.05), as was its effect on maladaptive coping strategies (-0.10, p < 0.05). Similarly, the direct effect of competence on adaptive coping strategies was significant (0.23, p < 0.01), as was its effect on maladaptive coping strategies (-0.33, p < 0.01). The direct effect of relatedness on adaptive coping strategies was non-significant (0.14, p>0.05), but significant for maladaptive coping strategies (-0.27, p<0.05). Additionally, the direct effect of adaptive and maladaptive coping strategies on avoidance coping was -0.32 and -0.40, respectively (p<0.01). The direct effect of adaptive coping strategies on pathological internet use was -0.19 (p<0.05), while the direct effect of maladaptive coping strategies was -0.11 (p<0.05). The direct effect of avoidance coping on pathological internet use was 0.37 (p<0.01). The study also found significant indirect effects of fundamental psychological needs on pathological internet use, with all three fundamental psychological needs (autonomy, relatedness, and competence) having indirect effects. However, emotion regulation strategies did not have significant direct effects on pathological internet use.6. ConclusionThe study findings indicate that problematic internet use is best explained by a causal model based on basic psychological needs, which are mediated by emotion regulation strategies and avoidant coping. This suggests that addressing basic psychological needs, as well as promoting healthy emotion regulation and coping strategies, could be effective strategies for reducing harmful internet use. It is important for therapists and counselors to consider these findings when designing interventions for problematic internet use.AcknowledgmentsWe appreciate all the participants and friends who supported us throughout this research project. We would like to extend our sincere gratitude to them for their valuable contribution to this study.